2021
DOI: 10.1111/jace.17567
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and electrical properties of Sr/Fe‐modified KNbO3 ferroelectric semiconductors with narrow bandgap

Abstract: In the process of exploring ferroelectric semiconductors, a new system of (1−x) KNbO3–xSrFeO3−δ (x = 0.00‐0.20) was successfully synthesized via solid‐state reaction. The crystal structures, ferroelectric, dielectric, optical, and electrical properties were systematically characterized. The orthorhombic phase with Amm2 space group is detected in all the ceramics. In addition, the orthorhombic and tetragonal phases coexist in 0.80KNbO3‐0.20SrFeO3‐δ ceramic. The decrease in oxygen octahedron distortion induces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The valences of K, Nb, and O ions in pure KN are in accordance with a previous report (Figure S3a−c). 39 The XPS spectra of 0.99KN−0.01BNB indicate the presence of Ba, Ni, and Bi ions (Figure S3g−i). To analyze the valence state of the Ni element in materials, the narrow-scan XPS spectrum of Ni 2p can be deconvoluted into two pairs of peaks, as shown in Figure S3h.…”
Section: Methodsmentioning
confidence: 99%
“…The valences of K, Nb, and O ions in pure KN are in accordance with a previous report (Figure S3a−c). 39 The XPS spectra of 0.99KN−0.01BNB indicate the presence of Ba, Ni, and Bi ions (Figure S3g−i). To analyze the valence state of the Ni element in materials, the narrow-scan XPS spectrum of Ni 2p can be deconvoluted into two pairs of peaks, as shown in Figure S3h.…”
Section: Methodsmentioning
confidence: 99%
“…In Fig. 6, we further compare the E g and P r of the KNLNST+1.3% Fe 2 O 3 ceramics fabricated in our work with those of the ferroelectric materials reported in the literature [6,9,14,[16][17][18]34,35,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. The detailed data for these materials are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 83%
“…Hence, the development of ferroelectric materials with both large P r and narrow E g is an urgent priority. Consequently, several new ferroelectric materials including Bi 0.98 Ca 0.02 Fe 0.95 Mn 0.05 O 3 (E g = 2.41 eV and P r = 92.5 μC/cm 2 ) [12], 0.8KNbO 3 -0.2SrFeO 3−δ (E g ≈ 2.18 eV and P r ≈ 2.5 μC/cm 2 ) [17], and PbTiO 3 -BiFeO 3 -Bi(Ni 1/2 Ti 1/2 )O 3 (PT-BF-BNT; E g = 2.25 eV and P r =32 μC/cm 2 ) [18] with narrow E g and large P r have recently been developed. However, the bandgaps of these reported ferroelectric materials are still above 2.0 eV, which is not beneficial to the absorption of visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have suggested that ferroelectricity and semiconducting behaviour can be simultaneously achieved in KN ceramics via Ni, Co and Fe modification. 12–14 The results of these studies provide a reference for the preparation of semiconducting KNbO 3 -based ferroelectrics. However, for most narrow-bandgap semiconducting ferroelectrics, further boosting the PHE activity through external electric fields is difficult because of the large leakage current and weakened ferroelectricity.…”
Section: Introductionmentioning
confidence: 91%